Health-Related Quality of Life in Pediatric Inflammatory Bowel Disease During COVID-19 Pandemic: A Prospective Study. Issue 5 (28th July 2022) - Fedele, Flora; Martinelli, Massimo; Strisciuglio, Caterina; Dolce, Pasquale; Giugliano, Francesca Paola; Scarpato, Elena; Staiano, Annamaria; Miele, Erasmo
Abstract : Objectives: The aims of our study were to evaluate health-related quality of life (HRQoL) in children affected by inflammatory bowel disease (IBD) during the first wave of Coronavirus disease 2019 (COVID-19) pandemic and after 12 months. Methods: This was a single-center, prospective, observational study conducted between April 2020 and April 2021. Children from 10 to 18 years with a confirmed diagnosis of IBD were enrolled during the first COVID-19–related national quarantine. The following information was collected at the baseline and after 12 months: IBD subtype, location and phenotype, disease activity, current and previous therapies. Patients were asked to complete the PROMIS Anxiety and IMPACT III questionnaires. Results: One hundred and eighteen patients were enrolled, of whom 54 (46%) were affected by Crohn disease (CD) and 64 (54%) with ulcerative colitis (UC; median age: 15.5 years, range 10.3–18; M/F: 68/50). Median HRQoL was significantly decreased after 12 months compared with the beginning of COVID-19–related quarantine (T1: 76.7 vs T2: 72.8; P < 0.001). At 12 months, a higher number of children were reported to be in active disease when compared with the enrollment [T2: 22/108 (20.4%) vs T1: 12/118 (10%); P = 0.02]. Multivariate analysis showed a significant influence on HRQoL of quarantine period ( P < 0.001), female sex ( P = 0.016), biologic therapy ( P = 0.011), and active disease ( P < 0.001). Conclusions: A deterioration of HRQoL after 12 months from COVID-19–related quarantine was observed. Additionally, the higher number of children with active disease at 12 months compared with enrollment may suggest detrimental consequences of the reduced disease control, contributing to decreased HRQoL.